Effect of Dehusking and Silk Removing Methods and Storage Temperatures on Fresh and Canned Babycorn - Teeranud Romphophak,; Jaroen Kunprom,; Suchera Yeangyuksakol,; Nitima Sanguansin,; Jingtair Siriphanich, (Agriculture and Natural Resources, 1993)
Methods of dehusking and silk removing in babycorn by hand or by forced air were compared. It was found that the appearance of fungi, the soluble solids content and the time used to dehusk and to remove babycorn silk was not significantly different among different methods. When babycorns were held in open air, after dehusking and silk removing before packing, the appearance of fungi increased with the increasing holding time. The study on the effect of temperature by packing babycorn on styrofoam tray covered with 20 pm. thicked PVC plastic film showed that babycorns were better kept at 3°C than at 1 or 5 °C. There were less growth of fungi and lower number of discolored babycorns (chilling injury) at this temperature. The soluble solids content and dry weight of babycorn decreased with time in storage at all temperatures. Storing babycorn in perforated plastic bags at 5°C for 0,1 and 2 weeks before canning in 4 % salt solution revealed that quality of canned babycorns were poorer after storage. They became darker in color, poorer in texture and off-flavor was also detected, particularly those stored longer than 7 days.